2012
DOI: 10.1097/qai.0b013e318249fe90
|View full text |Cite
|
Sign up to set email alerts
|

Retention in Care of Adults and Adolescents Living With HIV in 13 US Areas

Abstract: Less than half of persons living with HIV had laboratory evidence of ongoing clinical care and only two thirds established care after diagnosis. Further assessments determining modifiable barriers to accessing care could assist with achieving public health targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
126
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 26 publications
8
126
7
1
Order By: Relevance
“…Observational studies suggest that approximately 62% of adolescents and young adults link to care within the first year of diagnosis. 35,39,40 Other studies indicate that adolescents and young adults are less likely to link and remain in care than older adults. [40][41][42] Some studies using different age ranges for analysis found no difference in linkage in younger adults.…”
Section: Linkage To Carementioning
confidence: 99%
“…Observational studies suggest that approximately 62% of adolescents and young adults link to care within the first year of diagnosis. 35,39,40 Other studies indicate that adolescents and young adults are less likely to link and remain in care than older adults. [40][41][42] Some studies using different age ranges for analysis found no difference in linkage in younger adults.…”
Section: Linkage To Carementioning
confidence: 99%
“…This is denoted in the language of the Institute of Medicine report, which refers to laboratory measures as "proxies" for encounter-based measures (9,17). The use of CD4+ cell counts and HIV-1 RNA measurements to denote retention may also be of concern, since monitoring frequency guidelines or state/local reporting practices for HIV-related laboratory measures may change in different populations (19,33). In particular, as guidelines continue to decrease the recommended frequency of laboratory monitoring among stable patients on antiretroviral therapy, the degree to which laboratorybased measures will underestimate the population of retained patients will increase.…”
Section: Ratio Of Odds Ratiosmentioning
confidence: 99%
“…Laboratory data have been widely used as surrogate measures when data on primary care encounters are unavailable, as is often the case in large surveillance studies using public health laboratory data or cross-sectional population-based surveys that sample across defined geographic areas (e.g., county or state surveys). Such measures have been shown to be good indicators of initial or overall access to clinical HIV care (17), but there are no longitudinal data regarding concordance between measures of retention defined by HIV primary care encounters and those using surrogate laboratory measures (6,9,18,19).…”
mentioning
confidence: 99%
“…This challenge appears to be greatest in the USA where, in 2008, only 63% of HIV-infected men who have sex with men (MSM) were established in care following HIV diagnosis and 48% retained in care year on year [6]. Consequently, it was estimated that only 19% of the 1.1 million adults living with HIV in the USA had an undetectable viral load, reducing their risk of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…However, even if early treatment for the diagnosed HIVpositive population is found to be clinically beneficial, there is continued uncertainty about a population-level prevention effect [5] that could be achieved if ART coverage were high enough to reduce 'community viral load' (CVL) [1]. This challenge appears to be greatest in the USA where, in 2008, only 63% of HIV-infected men who have sex with men (MSM) were established in care following HIV diagnosis and 48% retained in care year on year [6]. Consequently, it was estimated that only 19% of the 1.1 million adults living with HIV in the USA had an undetectable viral load, reducing their risk of transmission.…”
mentioning
confidence: 99%